Integration in the European Union as a double-edge sword for the Western Balkans - Makrevska disoska, Elena (Institute for Research and European Studies-Bitola, 2017)
By analyzing the impact of the economic crisis on the Western Balkan (WB) countries, the paper concludes that their export, inflow of remittances and FDI have suffered due to the crisis. Regarding the rapid credit growth in years before the crisis it spurred an increase in imports, which in context of relatively uncompetitive economies, led to increased current account deficits despite significant remittances and FDI inflows. The impact of the crisis in the region can be explained mainly by their degree of European integration. But, the European Union (EU) is more uncertain to embrace the economically weaker countries, causing loss of EU credibility. It seems that the EU integration is a double-edged sword for the WB: in good times EU delivers its prosperity, but at a time of crisis, it is creating instability.
Keywords: economic crisis; transmission channel; Western Balkans; European Union